Solway country : land, life and livelihood in the Western border region of England and Scotland - Scott, Allen J. (Cambridge Scholars Publishing, 2015)
The Solway Country-the lands surrounding the inner Solway Firth-constitutes one of the many small regional worlds of the British Isles that are remarkable for the ways in which their landscapes evoke a powerful sense of territorial identity rooted not only in their physical appeal, but also in the richness and distinctiveness of their human history and geography. The Solway Country is an archetypical but hitherto little known exemplar of places like these. This book captures the spirit and substance of the Solway Country's allure by means of a series of layered narratives dealing with its natu.